Alih Fungsi Harta Benda Wakaf Dalam Perspektif Hukum Islam Dan Undang-Undang Perwakafan Di Indonesia - Dasrianto, Vito; Mahmudi, Elva; Arminsyah, Arminsyah (Jurnal Ilmiah Al-Hadi; Vol 9 No 1 (2023): Juli - Desember, 2023)
This objective discusses the transfer of functions of waqf assets in the perspective of Islamic law and waqf law in Indonesia. In the fiqh literature, there is a difference of opinion among scholars regarding the prohibition of selling or converting waqf assets. Some scholars interpret this prohibition literally, thus arguing that waqf assets, such as mosques and mosque equipment, may not be sold or exchanged, even if they are no longer usable. However, there are scholars who understand that the prohibition only applies to waqf that can still be utilised, while old waqf that is no longer useful may be sold or exchanged. This opinion is particularly adopted by scholars who follow the school of Ahmad bin Hanbal, as explained in Ibn Qudamah's al-Muqni. Meanwhile, the Constitution of Islamic Law (KHI) explains that waqf assets basically cannot be changed or used other than the waqf pledge. However, there is a dispensation mechanism that allows the transfer of the function of waqf property with the approval of the sub-district Religious Affairs Office, the Sub-district Ulema Council, and the local Sub-district Head, provided that the reason for the transfer is in accordance with the public interest or because the waqf property is no longer in accordance with the waqf pledge. Waqf Law No. 41/2004 also regulates the transfer of waqf property functions. In principle, waqf assets are prohibited from being used as collateral, confiscated, granted, sold, inherited, donated, and transferred in other forms. However, there is an exception if the waqf asset is used for the public interest in accordance with the general spatial plan and does not conflict with Islamic law. Waqf assets that undergo a change in status must be exchanged for assets that have at least the same benefits and exchange value as the original waqf assets.